2015
DOI: 10.3390/jlpea5040257
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable RF Energy Harvester with Customized Differential PCB Antenna

Abstract: In this work, a RF Energy harvester comprised of a differential RF-DC CMOS converter realized in ST130nm CMOS technology and a customized broadband PCB antenna with inductive coupling feeding is presented. Experimental results show that the system can work with different carrier frequencies and thanks to its reconfigurable architecture the proposed converter is able to provide a regulated output voltage of 2 V over a 14 dB of RF input power range. The conversion efficiency of the whole system peaks at 18% unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…During the last years, several proposals of power management units for harvesting energy from a single transducer have been reported. The most common sources of energy are light [3], mechanical vibrations [4], thermal gradients [5] and radio frequency (RF) waves [6]. However, these techniques are restricted to applications where a relatively constant supply of the energy source employed is granted.…”
Section: Hybrid Energy Harvestingmentioning
confidence: 99%
“…During the last years, several proposals of power management units for harvesting energy from a single transducer have been reported. The most common sources of energy are light [3], mechanical vibrations [4], thermal gradients [5] and radio frequency (RF) waves [6]. However, these techniques are restricted to applications where a relatively constant supply of the energy source employed is granted.…”
Section: Hybrid Energy Harvestingmentioning
confidence: 99%
“…Although this topology suffers from some loss caused by the leakage current, but in terms of overall performance, this topology is considered the best in terms of PCE if the input power is low. Because of its higher sensitivity compared with others, this topology is widely used in previously reported works …”
Section: Characterization and Analysis Of Rectifier Circuitsmentioning
confidence: 99%
“…State‐of‐the‐art CMOS rectifiers for 915 MHz RFID show an output load range from 10 kΩ to 5.45 MΩ. The DC output power ranges from 0.2 to 50 μW whereas the reference voltage are between 0.53 and 2.75 V . For 5.8 GHz, only the work of Radiom et al can be referred to with an output load of 5.45 MΩ.…”
Section: Ultrasmall Antenna To Be Combined With the Rectifiermentioning
confidence: 99%
See 1 more Smart Citation
“…The most common selected sources of energy are light [3,4], thermal gradients [5], mechanical vibrations [6][7][8] and radio frequency (RF) signals [9]. However, it has been observed that due to ambient variations, single harvesting sources can exhibit long periods of energy shortage, which reduces their overall dependability.…”
Section: Introductionmentioning
confidence: 99%